PARAMETER Study: LCZ696 Safe and Effective in Reducing Systolic and Pulse Pressure. Issue 28 (29th October 2015) - Zarifyan, Alla
Results of the PARAMETER study demonstrated that the angiotensin receptor neprilysin inhibitor LCZ696 reduced central aortic systolic and pulse pressure more effectively than olmesartan in older patients with systolic hypertension and arterial stiffness. Both treatments were safe and well tolerated without significantly variability in key safety parameters between the groups.